دراسة أثر التقييد العرضي لمساند البنى الفوقية لنماذج جسور السكك الحديدية على السلوك الديناميكي لركائزها تحت تأثير الحمولات الزلزالية - طريفي, زكائي; منصور, نزيه; خضّور, محمد (Latakia University Journal -Engineering Sciences Series, 2019)
أنجزت هذه الدراسة على نموذجين من الجسور البيتونية للسكك الحديدية، الأول منفّذ في المنطقة الداخلية السورية على بعد Km 13.6 من محطة دير الزور على محور سـكة حديد دير الزور– الطابية، أما الثاني فقد شُيّد في المنطقة الساحلية فوق نهر البدواي على محور سكة حديد العكاري – طرابلس. نفّذت مسـاند البنية الفوقية للنموذج الأول من النيوبرين بحيث تسـمح بحركتها المحدودة في كافة الاتجاهات عند خضوعها لتأثير الهزّات الزلزالية الأمر الذي سـيزيد القوى الجانبية، وعزوم الانعطاف القاعدية لركائزه، أما مسـاند النموذج الثاني، فكانت معدنية أسطوانية مما يُنقص القوى والعزوم المذكورة على ركائز هذا النموذج. أظهرت نتائـج هذا البحث أنه من الممكن تخفيض القوى والعزوم المذكورة بإنقاص كتلة البنيـة الفوقية للجسـر المسـاهمة في اهتزاز ركائزه عرضيا" لدى خضوعه للزلازل وذلك بتقييد حركة مساندها بهذا الاتجاه. This study was conducted on two concrete railway bridge types; the first was structured in the Syrian internal zone 13.6 Ks off Deir Alzor station on Deir Alzor – Tabieh railway axis, while the second was structured in the coastal zone over Baddawi river on Akkari – Tripoli railway axis. Superstructure bearings of the first type were made of neoprene which allows them to have a restricted movement in all directions when exposed to seismic effects, which will increase the basic lateral force and moments of the piers, while bearings of the second were made of cylindrical metal, and that will decrease the forces and moments of this type of piers. Results of this study show that the aforementioned force and moments may reduce by decreasing bridge Superstructure mass contributing to the vibration of its piers laterally upon exposure to earthquakes by constraining movement of its bearings in this direction.